Preventing and Countering Violent Extremism: Lessons from Selected Muslim Countries - Mohd Mizan Aslam (Islam Realitas: Journal of Islamic and Social Studies, 2020)
This paper explains the efforts of three Muslim countries, namely Yemen, Saudi Arabia and Malaysia in preventing and fighting against violence from jihadist extremism groups. De-radicalization program is understood as a process of changing the attitudes of former prisoners of terrorism to reject radicalism as a religious or political ideology that destroys national stability, and affects political and economic stability and even threatens human life. By using a qualitative approach, it was found that many countries have taken a significant approaches in dealing with the threat of terrorism through de-radicalization programs, especially in Yemen, Saudi Arabia and Malaysia. Most de-radicalisation programs are based on education and recovery. Education has the character of correcting misconceptions of politics and religion in militant activities, while the recovery strategy is more about continuous monitoring after liberation. The deradicalisation module aims at assisting these contries in militant recovery activities and also support their personal development. This paper explains the theoretical methods used in the de-radicalization programs in these three Islamic countries in the rehabilitation program. These countries use a set of tools that considers relevant factors such as holistic personality, self-reflection, social skills, criminal behavior, spirituality, security, and psychology.Tulisan ini menjelaskan bagaimana upaya pencegahan dan perlawanan terhadap kekerasan kelompok ekrimisme Jihadis berdasarkan pengalaman 3 negara Muslim yaitu Yemen, Saudi Arabia dan Malaysia.   Program deradikalisasi dipahami sebagai proses mengubah perilaku tahanan terrorisme untuk menolak radikalisme sebagai ideologi agama atau politik yang merusak stabilitas nasional, dan berpengaruh terhadap kestabilan politik dan ekonomi dan bahkan ancaman kepada kehidupan manusia. Dengan menggunakan pendekatan kualitatif, ditemukan bahwa banyak negara telah mengambil pendekatan yang signifikan dalam menghadapi ancaman terrorisme melalui program deradikalisasi terutama di Yemen, Saudi Arabia dan Malaysia. Kebanyakkan program deradikalisasi berasaskan pendidikan dan pemulihan. Pendidikan bersifat memperbaiki salah faham konsep berpolitik dan beragama dalam aktiviti militan, manakala strategi pemulihan lebih kepada pemantauan secara berterusan selepas pembebasan. Modul deradikalisasi bertujuan membantu kerajaan dalam kegiatan pemulihan militan dan juga membantu pembinaan personaliti mereka. Tulisan ini juga menjelaskan teoritikal metod yang digunakan dalam program deradikalisasi di tiga buah negara Islam ini dalam program rehabilitasi dengan menggunakan pendekatan personaliti holistik, pembinaan kendiri, skil-sosial, penjenayahan, kerohanian, toleransi, keselamatan dan psikologi.